Optimization of shopping center construction under organizational and financial constraints (Academic journal Industrial Machine Building Civil Engineering, 2019)
The article presents the results of optimizing the construction duration of the object and the average monthly financing intensityof the shopping center construction under organizational and financial constraints, namely: the work processes alignment– 68-76%; the maximum monthly financing intensity – 40 million UAN; number of work brigades – 1-2; the maximum constructionduration – 360 days. There were developed the method for optimizing and the results of numerical modeling of organizationaland financial decisions were obtained. The most efficient models of construction were identified by graphicalway under limited conditions of their implementation.
Keywords: organization of construction; civil engineering; trade and entertainment center; the duration; the intensity of the funding